A comparison of the levels of satisfaction with the medical services provided by primary healthcare centers in selected communes - Przybylska, Daria; Przybylski, Piotr; Drop, Bartłomiej; Czarnocki, Krzysztof; Przybylski, Wojciech; Drop, Katarzyna; Quinton, Magdalena (Polish Journal of Public Health, 2016)
Introduction. Family medicine remains the primary type of medical services in Poland and it is supposed to treat both individual patients and the society as a whole. Due to the growing commercialization of the health service, most primary healthcare centers have transformed into non-public healthcare facilities. The public ones (called SPZOZ in Polish) account only for a small fraction of the whole number of primary healthcare facilities. The quality of medical services provided by such facilities, as patients see it, remains one of the key elements determining the development of family medicine centers. Aim. The aim of this paper was to assess patient satisfaction levels regarding the healthcare services they received in two primary healthcare institutions, both of the NZOZ and SPZOZ type, in a small town located close to Lublin. Material and methods. An anonymous survey was filled out by 30 patients of both a public and non-public healthcare center located in Niemce (Niemce Commune, Lublin District). The quality of services was assessed using an original questionnaire in the form of a poll. Results. The results obtained indicate a clear relationship between one’s trust to the physician, diagnosis accuracy and visiting the particular center again, in order to continue the treatment. For older subjects, it was nurses’ kindness and politeness that was the most important. The elderly appreciated the kindness and politeness of the nurses in particular. No significant differences were found between the institutions in respect of the overall perception of satisfaction with services. In terms of infrastructure assessment, the majority of positive feedback was provided for NZOZ. Conclusions. The findings above suggest that it is essential to conduct surveys on a regular basis, in order to check patients’ assessment of the service quality in various institutons.